Swarm, Evolutionary, and Memetic Computing First International Conference on Swarm, Evolutionary, and Memetic Computing, SEMCCO 2010, Chennai, India, December 16-18, 2010. Proceedings - Panigrahi, Bijaya Ketan; Das, Swagatam; Suganthan, Ponnuthurai Nagaratnam; Dash, Subhransu Sekhar; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the First International Conference on Swarm, Evolutionary, and Memetic Computing, SEMCCO 2010, held in Chennai, India, in December 2010. The 86 revised full papers presented were carefully reviewed and selected from 225 submissions.
Self-adaptive Differential Evolution with Modified Multi-Trajectory Search for CEC$1 (B2010 Large Scale Optimization -- Differential Evolution Based Ascent Phase Trajectory Optimization for a Hypersonic Vehicle -- Dynamic Grouping Crowding Differential Evolution with Ensemble of Parameters for Multi-modal Optimization -- Empirical Study on Migration Topologies and Migration Policies for Island Based Distributed Differential Evolution Variants -- Differential Evolution Based Fuzzy Clustering -- A Population Adaptive Differential Evolution Strategy to Light Configuration Optimization of Photometric Stereo -- Solving Multi Objective Stochastic Programming Problems Using Differential Evolution -- Multi Sensor Fusion Using Fitness Adaptive Differential Evolution -- Differential Evolution Algorithm with Ensemble of Parameters and Mutation and Crossover Strategies -- Design of Robust Optimal Fixed Structure Controller Using Self Adaptive Differential Evolution -- Electromagnetic Antenna Configuration Optimization Using Fitness Adaptive Differential Evolution -- Analyzing the Explorative Power of Differential Evolution Variants on Different Classes of Problems -- A Self Adaptive Differential Evolution Algorithm for Global Optimization -- Optimization for Workspace Volume of 3R Robot Manipulator Using Modified Differential Evolution -- Adaptive Differential Evolution with p-Best Crossover for Continuous Global Optimization -- A New Particle Swarm Optimization Algorithm for Dynamic Environments -- Power Mutation Embedded Modified PSO for Global Optimization Problems -- PSO Advances and Application to Inverse Problems -- Adaptive and Accelerated Exploration Particle Swarm Optimizer (AAEPSO) for Solving Constrained Multiobjective Optimization Problems -- Expedite Particle Swarm Optimization Algorithm (EPSO) for Optimization of MSA -- Covariance Matrix Adapted Evolution Strategy Based Design of Mixed H2/H??? PID Controller -- Towards a Link between Knee Solutions and Preferred Solution Methodologies -- A Relation-Based Model for Convergence Analysis of Evolutionary Algorithm -- Neural Meta-Memes Framework for Combinatorial Optimization -- An Improved Evolutionary Programming with Voting and Elitist Dispersal Scheme -- Heuristic Algorithms for the L(2,1)-Labeling Problem -- Runtime Analysis of Evolutionary Programming Based on Cauchy Mutation -- Best Hiding Capacity Scheme for Variable Length Messages Using Particle Swarm Optimization -- Ant Colony Optimization for Markowitz Mean-Variance Portfolio Model -- Hybrid PSO Based Integration of Multiple Representations of Thermal Hand Vein Patterns -- Detection and Length Estimation of Linear Scratch on Solid Surfaces Using an Angle Constrained Ant Colony Technique -- An Intelligence Model with Max-Min Strategy for Constrained Evolutionary Optimization -- Parallel Ant-Miner (PAM) on High Performance Clusters -- A Software Tool for Data Clustering Using Particle Swarm Optimization -- An ACO Approach to Job Scheduling in Grid Environment -- Runtime Analysis of (1+1) Evolutionary Algorithm for a TSP Instance -- An Evolutionary Approach to Intelligent Planning -- Substitute Domination Relation for High Objective Number Optimization -- Discrete Variables Function Optimization Using Accelerated Biogeography-Based Optimization -- A Genetic Algorithm Based Augmented Lagrangian Method for Computationally Fast Constrained Optimization -- Evolutionary Programming Improved by an Individual Random Difference Mutation -- Taguchi Method Based Parametric Study of Generalized Generation Gap Genetic Algorithm Model -- EBFS-ICA: An Efficient Algorithm for CT-MRI Image Fusion -- Adaptive Nonlinear Signal Approximation Using Bacterial Foraging Strategy -- Swarm Intelligence for Optimizing Hybridized Smoothing Filter in Image Edge Enhancement -- A Hybrid GA-Adaptive Particle Swarm Optimization Based Tuning of Unscented Kalman Filter for Harmonic Estimation -- Using Social Emotional Optimization Algorithm to Direct Orbits of Chaotic Systems -- A Hybrid ANN-BFOA Approach for Optimization of FDM Process Parameters -- Bio Inspired Swarm Algorithm for Tumor Detection in Digital Mammogram -- A Hybrid Particle Swarm with Differential Evolution Operator Approach (DEPSO) for Linear Array Synthesis -- Sensor Deployment in 3-D Terrain Using Artificial Bee Colony Algorithm -- Novel Particle Swarm Optimization Based Synthesis of Concentric Circular Antenna Array for Broadside Radiation -- A Particle Swarm Optimization Algorithm for Optimal Operating Parameters of VMI Systems in a Two-Echelon Supply Chain -- Enhanced Memetic Algorithm for Task Scheduling -- Quadratic Approximation PSO for Economic Dispatch Problems with Valve-Point Effects -- Fuzzified PSO Algorithm for OPF with FACTS Devices in Interconnected Power Systems -- Co-ordinated Design of AVR-PSS Using Multi Objective Genetic Algorithm -- A Genetic Algorithm Approach for the Multi-commodity, Multi-period Distribution Planning in a Supply Chain Network Design -- Particle Swarm Optimization with Watts-Strogatz Model -- Multi-objective Evolutionary Algorithms to Solve Coverage and Lifetime Optimization Problem in Wireless Sensor Networks -- Offline Parameter Estimation of Induction Motor Using a Meta Heuristic Algorithm -- Performance Evaluation of Particle Swarm Optimization Based Active Noise Control Algorithm -- Solution to Non-convex Electric Power Dispatch Problem Using Seeker Optimization Algorithm -- Swarm Intelligence Algorithm for Induction Motor Field Efficiency Evaluation -- Artificial Bee Colony Algorithm for Transient Performance Augmentation of Grid Connected Distributed Generation -- Performance Comparison of Attribute Set Reduction Algorithms in Stock Price Prediction - A Case Study on Indian Stock Data -- Dimensionality Reduction and Optimum Feature Selection in Designing Efficient Classifiers -- Social Emotional Optimization Algorithm for Nonlinear Constrained Optimization Problems -- Multi-Objective Optimal Design of Switch Reluctance Motors Using Adaptive Genetic Algorithm -- Genetic Algorithm Approaches to Solve RWA Problem in WDM Optical Networks -- Multi-objective Performance Optimization of Thermo-Electric Coolers Using Dimensional Structural Parameters -- An Artificial Physics Optimization Algorithm for Multi-Objective Problems Based on Virtual Force Sorting Proceedings -- Effective Document Clustering with Particle Swarm Optimization -- A Hybrid Differential Invasive Weed Algorithm for Congestion Management -- Security Constrained Optimal Power Flow with FACTS Devices Using Modified Particle Swarm Optimization -- Tuning of PID Controller Using Internal Model Control with the Filter Constant Optimized Using Bee Colony Optimization Technique -- An Efficient Estimation of Distribution Algorithm for Job Shop Scheduling Problem -- Semantic Web Service Discovery Algorithm Based on Swarm System -- Stochastic Ranking Particle Swarm Optimization for Constrained Engineering Design Problems -- A New Improved Particle Swarm Optimization Technique for Daily Economic Generation Scheduling of Cascaded Hydrothermal Systems -- Improved Real Quantum Evolutionary Algorithm for Optimum Economic Load Dispatch with Non-convex Loads -- Linear Array Geometry Synthesis with Minimum Side Lobe Level and Null Control Using Dynamic Multi-Swarm Particle Swarm Optimizer with Local Search -- Constraint Handling in Transmission Network Expansion Planning -- A Novel Multi-objective Formulation for Hydrothermal Power Scheduling Based on Reservoir End Volume Relaxation -- Particle Swarm Optimization and Varying Chemotactic Step-Size Bacterial Foraging Optimization Algorithms Based Dynamic Economic Dispatch with Non-smooth Fuel Cost Functions -- Hydro-thermal Commitment Scheduling by Tabu Search Method with Cooling-Banking Constraints.s
Keywords: Computer science; Computer Communication Networks; Computer software; Artificial intelligence; Optical pattern recognition; Computer Science; Computation by Abstract Devices; Artificial Intelligence (incl. Robotics).; Algorithm Analysis and Problem Complexity; Pattern Recognition; Computer Communication Networks; Programming Techniques